Medical Practitioners' use of genetic counselling services in Cape Town - Pretorius, Willem (Department of Clinical Laboratory Sciences, 2024)
The genetic counselling profession has grown exponentially in the last decade. Major advances in genetic technologies contributed to the increased need for these professionals. In South Africa, medical practitioners in private practice are increasingly making use of the services of genetic counsellors in the routine clinical management of their patients. In this research study medical practitioners in private practice in Cape Town, who actively utilise genetic counselling services, were recruited to investigate why they make use of genetic counselling services. A total of twelve medical practitioners were recruited for online semi-structured interviews in Afrikaans or English. The interviews were transcribed, and data was analysed using thematic analysis. From the interviews three broad themes were identified namely: the identity of genetics and genetic counselling services, resource limitations, and the appreciable impact of genetic counselling. Some interesting points of discussion included practitioners' views on direct-to-consumer testing platforms and the ambiguity around the professional title of a genetic counsellor. This research study is, according to our knowledge, one of the first global attempts to interview medical practitioners specifically who actively make use of genetic counselling services. It provides insights that could be used to promote the service throughout South Africa and other countries across the world. Future research that includes the perspectives of medical practitioners throughout South Africa would allow for even greater perspective on utilising genetic counselling services.